2016
DOI: 10.1190/int-2015-0017.1
|View full text |Cite
|
Sign up to set email alerts
|

Seismic attributes for description of reef growth and channel system evolution — Case study of Intisar E, Libya

Abstract: A 3D seismic survey over the Intisar E field in the Ajdabiya Trough of the Sirte Basin, Libya, revealed a channel-like feature in Eocene carbonates that wraps around the pinnacle reef that contains the reservoir. We have used coherence, curvature, and spectral decomposition seismic attributes to determine the morphology and gray-level co-occurrence matrix attributes to define seismic facies within the feature. These indicated that the channel originated by submarine scouring caused by downslope movement of tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Instead, a sophisticated investigation approach is needed to depict the vertical and lateral differences in reservoir properties even in case of small-scale variations. As shown by numerous oil and gas exploration studies, 3D reflection seismic surveys can not only deliver structural information, but also important reservoir properties, e.g., elastic parameters and a variety of seismic attributes (Pussak et al 2014;Marfurt 2015;Wang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, a sophisticated investigation approach is needed to depict the vertical and lateral differences in reservoir properties even in case of small-scale variations. As shown by numerous oil and gas exploration studies, 3D reflection seismic surveys can not only deliver structural information, but also important reservoir properties, e.g., elastic parameters and a variety of seismic attributes (Pussak et al 2014;Marfurt 2015;Wang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…variance and chaos) are able to image vertical and lateral discontinuities, and can therefore highlight stratigraphic and structural boundaries like faults, fractures, dolines, and reef edges (Chopra & Marfurt, 2007). For the variance, a trace-by-trace analysis is performed in order to quantify the dissimilarity of the seismic waveform of neighboring traces within a specified time window (Bahorich & Farmer, 1995;Marfurt et al, 1998;Wang et al, 2016). Chaos is a similar attribute that maps the 'chaoticness´of the seismic signal from statistical analysis of dip/azimuth estimates.…”
Section: Seismic Single-attribute Analysismentioning
confidence: 99%
“…at the Leduc carbonate reef bank in Canada and the Tor Field area in the North Sea. Furthermore, Wang et al (2016) used seismic attributes to describe the reef growth and the evolution of channel systems for Eocene carbonates in the Sirte Basin in Libya. Edge-or discontinuity detection attributes, like variance and chaos, have been used to conduct a small-scale seismic-based fracture analysis (Jaglan et al, 2015;Williams et al, 2017;Albesher et al, 2020;Boersma et al, 2020;Loza Espejel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Integrating geological and geophysical data to determine nine facies of reservoir units southeast of the Ajdabiya Trough, Abdelnabi et al [7] observed that faults mostly control the distribution and thickness of one of the reservoir units. A 3D (three-dimensional) seismic survey [8] showed a channel-like feature (of submarine origin) within the southern part of the trough (called the Intisar E field). Some pinnacle reefs in the Intisar complex contained hydrocarbon reservoirs while adjacent reefs are barren due to a cut in the channel that supplied carbonate debris in the late stages of the reefs' growth [8].…”
Section: Introductionmentioning
confidence: 99%
“…A 3D (three-dimensional) seismic survey [8] showed a channel-like feature (of submarine origin) within the southern part of the trough (called the Intisar E field). Some pinnacle reefs in the Intisar complex contained hydrocarbon reservoirs while adjacent reefs are barren due to a cut in the channel that supplied carbonate debris in the late stages of the reefs' growth [8]. Submarine scouring caused turbidity currents through the channel that resulted in carbonate sedimentation in the hydrocarbon reservoirs [8].…”
Section: Introductionmentioning
confidence: 99%